Case report: A co-existing case of ulcerative colitis and dysferlinopathy in a male patient - Li, Limin; Yan, Qiong; Deng, Mingming; Lü, Muhan; Zhou, Tiejun; Zhong, Xiaolin (Frontiers in Medicine, 2025)
Patients with inflammatory bowel disease (IBD) are at risk of developing malnutrition, severe dystrophic muscle weakness, and muscle atrophy. We present a case of a 33-year-old male patient who exhibited concurrent muscle atrophy, muscle weakness, diarrhea, and mucopurulent bloody stools. Notably, the patient reported that his household or family members experienced similar symptoms of muscle weakness, without any apparent neurological or psychiatric manifestations. The patient’s intestinal symptoms were most consistent with ulcerative colitis, while the muscle weakness originated from dysferlinopathy following a comprehensive diagnostic work-up. The patient was initiated on vedolizumab therapy and L-carnitine therapy, and his symptoms improved after 1 month of follow-up. This case study underscores the necessity for clinicians to maintain a high level of suspicion for the presence of concomitant diseases when encountering IBD patients with muscle weakness. This approach is essential for achieving an early diagnosis and treatment.